Belkiss Spenzieri: uma fotobiografia (1928-2005) - Freire, Luciana Bueno de Alvarenga (2018)
This study deals with the narrative of the life history of the Goianist musician Belkiss Spenzieri, through the analysis of hers photographs, correlating them with others photos of the same period. Belkiss was born in the city of Goiás-GO in 1928 and she was raised and encouraged by her grandmother, Nhanhá do Couto, in the field of music, she moved to Goiania-GO in 1940, when she gave her first public recital at the age of 12. In 1942, her grandmother and she went to Rio de Janeiro-RJ, so that Belkiss could study at the School of Music of the University of Brazil. In 1945, after graduating and the death of her grandmother, the musician returned to Goiânia to create a Conservatory of Music in Goiás, as it had always been Nhanha's dream. Thus, she married in 1946, had two children and, in 1956, created the Conservatory of Music, but the federal recognition of it only occurred in 1959, with the authorization of Juscelino Kubitschek. Belkiss was acclaimed director of the conservatory from its foundation and after its integration with the UFG, in 1960. And so she continued her career as a teacher and as a musician, always researching Brazilian music and spreading the national composers. She died in 2005, aged 77, in the city of Goiânia. Throughout her life she was photographed, in Brazil and abroad. Therefore, the parallel with this photobiography was with the photographers who photographed her, and the way of doing portraiture in this period of her existence. Several theorists were used but, during the analysis of the photographs, the methodology of Arthur Freitas (2004) was highlighted, under the biases of the social, formal and semantic perspectives proposed by him.